2011
DOI: 10.1055/s-0031-1282359
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Development of Zein Antimicrobial Edible Film and Essential oil of Zataria multiflora Boiss. on Salmonella enteritidis, Listeria monocytogenes, Escherichia coli and Staphylococcus aureus

Abstract: Zataria multiflora Boiss' essential oil is a natural product that would be able to effect on food-borne bacteria. In this research ethanol based antimicrobial zein edible films containing added 0.00, 0.50, 1.00, 1.50, 2.00 % (w/v) Zataria multiflora and glycerol as a plasticizer were created. The films were effective against Salmonella enteritidis, Listeria monocytogenes, Escherichia coli 0157: H7 and Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Discussion Z. multiflora has several biological and pharmacological properties. ZM is acted as an antimicrobial in the food industry (14)(15)(16)(17) and used as an antispasmodic, anesthetic agent in Iranian traditional medicine (14). There are many studies that show that Z. multiflora has antibacterial (9) antifungal and antioxidant (7,8) activities.…”
Section: Resultsmentioning
confidence: 99%
“…Discussion Z. multiflora has several biological and pharmacological properties. ZM is acted as an antimicrobial in the food industry (14)(15)(16)(17) and used as an antispasmodic, anesthetic agent in Iranian traditional medicine (14). There are many studies that show that Z. multiflora has antibacterial (9) antifungal and antioxidant (7,8) activities.…”
Section: Resultsmentioning
confidence: 99%
“…Acidic nature of the hydroxyl group in thymol and carvacrol and the involvement of the hydroxyl group in the formation of hydrogen bonds may explain the highest antimicrobial activity (31). Investigations showed that Z. multiflora EO can inhibit food-borne pathogenic microorganisms such as Staphylococcus aureus (33), Bacillus cereus (34), Sallmonella typhimurium (17), Listeria monocytogenes (18) and Aspergillus flavus (19). Mansour et al (2010) showed that S. aureus was more sensitive than other tested bacteria (MIC 0.039 % (w/v)) and Streptococcus pyogenes and Proteus mirabilis (MIC 0.156 % (w/v)) were the most resistant bacteria (35).…”
Section: Discussionmentioning
confidence: 99%
“…(10), Pulicaria gnaphalodes (11), Trachyspermum ammi (12) and Cuminum cyminum (13,14,15) EOs and also on the antibacterial activity of Artemisia absinthium (16), Zataria multiflora Boiss. (17,18,19), Pulicaria gnaphalodes (20), Trachyspermum ammi (21) and Cuminum cyminum (15) EOs on some food-borne and pathogenic microorganisms. In spite of the importance and long-term use of Trachyspermum ammi, Pulicaria gnaphalodes and Artemisia absinthium, no work has been carried out on the antimicrobial activity of these EOs on pathogenic and non-pathogenic V. parahaemolyticus.…”
mentioning
confidence: 99%
“…Decimal dilutions are made to give a concentration of ca 10 6 cfu/ml. From this a volume of 500 µl was used to inoculate the broth combinations to give a final concentration of ca 10 4 cfu/ml (Ghasemi et al, 2012).…”
Section: Inoculum Preparationmentioning
confidence: 99%
“…According to Ghasemi et al (2012) study, there was a decline in the growth of microorganisms by increased concentration of ZEO. Salmonella enteritidis, Listeria monocytogenes, E. coli and S. aureus showed significant reductions in bacterial survival in the higher ZEO concentration.…”
Section: Introductionmentioning
confidence: 99%